PERSEPSI MAHASISWA STIT AL IBROHIMY BANGKALAN TERHADAP PENGGUNAAN CHATGPT SEBAGAI ALAT BANTU PENULISAN TUGAS KULIAH - Fauzi, Muhammad; Arifin, Moh. Samsul (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2024)
The digital era has brought urgent changes to the world of education, one of which is the utilization of artificial intelligence (AI) technologies such as ChatGPT. This technology can assist students in various academic aspects, especially in writing assignments. This study aims to explore the perceptions of students at STIT Al Ibrohimy Bangkalan regarding the use of ChatGPT as a tool to aid in writing assignments, focusing on aspects of effectiveness, ease of use, and ethical considerations within the context of education based on Islamic values. This research adopts a Mixed Methods approach, combining both qualitative and quantitative methods. For the qualitative aspect, data were collected through in-depth interviews with students and observations of their use of ChatGPT in academic activities. This qualitative approach provides a deeper understanding of students' experiences and perceptions regarding the use of ChatGPT in completing assignments. On the other hand, quantitative data were gathered through a questionnaire designed to measure the frequency of use, effectiveness, and efficiency of ChatGPT based on students' perceptions. The results show that most students find ChatGPT effective in speeding up the assignment writing process; however, they also acknowledge the importance of verifying the accuracy of the information provided. This study contributes to understanding the use of technology in the learning process and offers recommendations for further development in the implementation of AI-based technologies in higher education.